PEMBIASAAN BR3T (BERSIH, RAPI, TERTIB, TERATUR DAN TERPELIHARA) DALAM MENANAMKAN PENDIDIKAN KARAKTER BAGI PESERTA DIDIK SEKOLAH DASAR - Annida Dwi Kirasti; Ari Sofia; Roy Kembar Habibi; Riswandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study focuses on the urgency of instilling character education in elementary school students through habitual activities in the school environment. One of the habitual methods applied is BR3T, which refers to cleanliness, neatness, order, regularity, and maintenance. The purpose of this study is to describe how the BR3T habit is implemented and its effect on character development of students at SD Negeri 2 Rajabasa Lama. The methodology used in this study is a qualitative approach with a case study technique. Participants in this study included the principal, educators, and students. Data collection was carried out using observation, interviews, and data collection methods. For data analysis, the Miles and Huberman model was used which includes data reduction, presentation, and drawing conclusions. The findings of the study indicate that the BR3T habit is implemented regularly through various activities at school, such as completing assignments on time, community service, lining up before entering class, maintaining order while studying, and caring for and maintaining school facilities, including watering plants, cleaning classrooms, and keeping the library tidy. Implementing this habit has shown a positive impact on students' character development, particularly in fostering discipline, responsibility, and cooperation. Therefore, BR3T can be an effective strategy for internalizing positive character values ​​in elementary school students.